2018
DOI: 10.1155/2018/5309490
|View full text |Cite
|
Sign up to set email alerts
|

Erchen Decoction Ameliorates Lipid Metabolism by the Regulation of the Protein CAV‐1 and the Receptors VLDLR, LDLR, ABCA1, and SRB1 in a High‐Fat Diet Rat Model

Abstract: Lipid metabolism disorder is a common metabolic disorder characterized by abnormal lipid levels in blood. Erchen decoction (ECD) is a traditional Chinese medicine prescription, which is used for the treatment of diseases caused by retention of phlegm dampness. It has been reported to ameliorate the disorder of lipid metabolism. The aim of the present study was to investigate the effects and underlying mechanisms of ECD in lipid metabolism disorder induced by a high-fat diet (HFD) in rats. ECD (4.35g/kg/d) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
3
9
0
Order By: Relevance
“…Compared with traditional dietary model, this animal model has a shorter time interval and is stable, which makes it ideal to study obesity. We found that ECD treatment could help the negative effects of obesity, including weight loss, improvements in IR, and the regulation of dyslipidemia, which is consistent with previous studies (Gao et al, 2015;Zhang et al, 2017;Ding et al, 2018;Zhang et al, 2020b;Lee et al, 2020) and illustrates that ECD has a regulatory effect on obesity caused by genetic factors. However, the regulatory effects of ECD on TC and HDL-C in blood lipids are not currently consistent, which might be related to the different models and drug concentrations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Compared with traditional dietary model, this animal model has a shorter time interval and is stable, which makes it ideal to study obesity. We found that ECD treatment could help the negative effects of obesity, including weight loss, improvements in IR, and the regulation of dyslipidemia, which is consistent with previous studies (Gao et al, 2015;Zhang et al, 2017;Ding et al, 2018;Zhang et al, 2020b;Lee et al, 2020) and illustrates that ECD has a regulatory effect on obesity caused by genetic factors. However, the regulatory effects of ECD on TC and HDL-C in blood lipids are not currently consistent, which might be related to the different models and drug concentrations.…”
Section: Discussionsupporting
confidence: 92%
“…ECD can promote the expression of CDKAL1 and improve the function of islet cells, thereby ameliorating insulin secretion (Gao et al, 2015). Moreover, the intervention effects by which ECD improves lipid metabolism include the inflammatory response (Lee et al, 2020) and lipid transport (Ding et al, 2018). The lipid metabolic balance is the result of a combination of lipogenesis and lipolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the body fluid accumulates, it is easy to produce phlegm, which can lead to vascular blockage. Animal studies showed that Erchen decoction (the same ingredients as HXZQ) could regulate the caveolae mRNA expression in rats fed with high-fat diet, lower the blood glucose, regulate the lipid metabolism, and reduce the insulin resistance; it also increased the expression of CDKAL1 MRNA and protein in mouse liver and subcutaneous fat and promoted the secretion of insulin [ 24 ]. In addition, glial cells first respond to AIS by upregulating transcription of early proinflammatory cytokines, such as TNF- α , leading to neuronal death and releasing neurotoxic substances into the bloodstream, further enhancing metalloproteinase expression [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for the potential mechanisms of ECD, only limited results have been obtained. Ding et al (2018) reported that ECD could ameliorate lipid metabolism by regulating the lipid transporters and their receptors (Gao et al, 2015), indicating that ECD could promote the CDKAL1 expression, ameliorate islet cell function, and raise insulin levels.…”
mentioning
confidence: 99%